INCREASING HIGHER-ORDER THINKING SKILL OF ELEMENTARY SCHOOL STUDENTS THROUGH PROBLEM-BASED LEARNING - Ully Fauziah; Yanti Fitria (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The era of the industrial revolution 4.0 requires students to have higher-order thinking skills in solving everyday problems. The purpose of this study was to determine the improvement of highorder thinking skills of elementary school students using problem-based learning. This research was a classroom action research conducted on 30 fifth grade students of SDN 05 Birugo. The results showed that the average score of students' initial ability was 45.00 with a percentage of completeness of 35%, in cycle 1 getting an average score of 58.00 with a percentage of completeness of 70% and in cycle 2 getting an average score of 75.00 with 80% completeness. The results showed an increase of high-order thinking skills of elementary school students using problem-based learning. The implications of this study can be used as a reference for improving Higher-Order Thinking Skills (HOTS) of elementary school students.